Ramucirumab in Indian Patients with Advanced Gastric Cancer—Does Borderline Performance Status and Heavy Burden of Disease in Real World Practice Impact Clinical Benefit? - Ramaswamy, Anant; Bajaj, Kripa; Talwar, Vineet; Prabhash, Kumar; Batra, Ullas; Dhabhar, Boman; Sharma, Mansi; Ghadyalpatil, Nikhil; CT, Satish; Goyal, Gautam; Muzamil, Javvid; Bhatt, Amit; Jain, Parveen; Ranade, Anantbhushan; Kamath, Mangesh; Gawande, Jayant Pundlik; Thippeswamy, Ravi; Mirani, Jimmy; Reddy, Neelesh; Ganguly, Sandip; Mishra, Sourav Kumar; Madabhavi, Irappa; HP, Shashidhara; Panda, Soumya Surath; Patil, Shekar; Bhargava, Prabhat; Ostwal, Vikas (South Asian Journal of Cancer, 2021)
Background Ramucirumab is considered a standard of care as second-line therapy (CT2) in advanced gastric cancers (AGCs). The aim of this study was to assess practice patterns and outcomes with ramucirumab among Indian patients with AGCs.Materials and Methods A computerized clinical data entry form was formulated by the coordinating center's (Tata Memorial Hospital) medical oncologists and disseminated through personal contacts at academic conferences as well as via email for anonymized patient data entry. The data was analyzed for clinical characteristics, response rates, and survival outcomes.Results A total of 26 physicians contributed data, resulting in 55 patients receiving ramucirumab and being available for analysis. Median age was 53 years (range: 26–78), 69.1% of patients had greater than two sites of disease, and baseline Eastern Cooperative Oncology Group's performance score (ECOG PS) ≥ 2 was seen in 61.8% of patients. Ramucirumab was used as monotherapy in 10.9% of patients, while the remaining 89.1% received ramucirumab combined with chemotherapy. Median event-free survival (EFS) and median overall survival (OS) with ramucirumab were3.53 months (95% CI: 2.5–4.57) and 5.7 months (95% CI: 2.39–9.0), respectively. Common class specific grade adverse events seen with ramucirumab included gastrointestinal (GI) hemorrhage (9.1% - all grades) and uncontrolled hypertension (Grade 3/4 - 3.6%).Conclusions Ramucirumab appears to have similar efficacy in Indian AGC patients when compared with real-world data from other countries in terms of median EFS, but OS appears inferior due to more patients having borderline ECOG PS and high metastatic disease burden. GI hemorrhages appear more common than published data, although not unequivocally related to ramucirumab.
Keywords: Ramucirumab; ECOG PS ≥ 2; advanced gastric cancer; India